Plasma and Urinary Heparin Cofactor II Levels in Patients with Nephrotic Syndrome - Grau, E; Oliver, A; Félez, J; Barceló, P; Fernandez, C; Ballarin, J A; Fontcuberta, J; Rutilant, M L I (Thrombosis and Haemostasis, 1988)
Heparin cofactor II (HC II) levels were measured by electroimmunoassay in plasmas and urines from 68 patients with nephrotic syndrome. In addition, antithrombin III (AT III) and protein C (PC) activities and antigens were measured also in the same group of patients. Seven of these patients had histories of thrombosis. Plasma HC II levels (mean ± SD 105 ± 43) were not different from levels in healthy subjects (94 ± 17). Only 5 patients had low plasma levels of HC II. None of the patients with thrombosis had low HC II levels. Even though measurable amounts of HC II were found in 25 urines from 50 patients. There was a relationship in the urinary excretion between HC II and AT III and their urinary clearances were quite similar. However, no correlation was found between plasma HC II and AT III levels, and levels of AT III activity and antigen were significantly lower than in healthy subjects. Three patients with hystories of thrombosis had low AT III levels. Most patients (including those with thrombosis histories) had high plasma PC levels and increased urinary loss.It is suggested that HC II does not play an important role in the pathogenesis of thrombosis in nephrotic syndrome.
Keywords: Heparin cofactor II; Antithrombin III; Protein C; Nephrotic syndrome